The prevalence of adverse cardiometabolic responses to exercise training with evidence-based practice is low - Dalleck LC (Dove Medical Press, 2015)
Lance C Dalleck,1 Gary P Van Guilder,2 Tara B Richardson,1 Chantal A Vella3 1Recreation, Exercise, and Sport Science Department, Western State Colorado University, Gunnison, CO, USA; 2Department of Health and Nutritional Sciences, South Dakota State University, Brookings, SD, USA; 3Department of Movement Sciences, WWAMI Medical Education Program, University of Idaho, Moscow, ID, USA Background: The purpose of this study was to determine the prevalence of individuals who experienced exercise-induced adverse cardiometabolic response (ACR), following an evidence-based, individualized, community exercise program. Methods: Prevalence of ACR was retrospectively analyzed in 332 adults (190 women, 142 men) before and after a 14-week supervised community exercise program. ACR included an exercise training-induced increase in systolic blood pressure of 10 mmHg, increase in plasma triglycerides (TG) of >37.0 mg/dL (0.42 mmol/L), or decrease in high-density lipoprotein cholesterol (HDL-C) of >4.0 mg/dL (0.12 mmol/L). A second category of ACR was also defined – this was ACR that resulted in a metabolic syndrome component (ACR-risk) as a consequence of the adverse response. Results: According to the above criteria, prevalence of ACR between baseline and post-program was systolic blood pressure (6.0%), TG (3.6%), and HDL-C (5.1%). The prevalence of ACR-risk was elevated TG (3.2%), impaired fasting blood glucose (2.7%), low HDL-C (2.2%), elevated waist circumference (1.3%), and elevated blood pressure (0.6%). Conclusion: Evidence-based practice exercise programming may attenuate the prevalence of exercise training-induced ACR. Our findings provide important preliminary evidence needed for the vision of exercise prescription as a personalized form of preventative medicine to become a reality. Keywords: evidence-based research, cardiovascular health, community-based research, metabolic health